BERDAKWAH DENGAN PENDEKATAN QURĀNI - Sitti Musyahidah (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2017)
Alqurān is not only a holy book for Muslims but also a guide in living a life to gain the happiness of the world and the hereafter. Alqurān not only contains teachings, knowledge and information, but also the reading and practice of the Qurān can be a way or approach to preach both to ourselves and others. The closer to the Qurān someone is, the more peace and happiness they will get. And that is the ultimate goal of da'wah.